High‐Speed Fabrication of Lithium‐Ion Battery Electrodes by UV‐Curing. Issue 5 (9th April 2015) - Xue, Zheng; Hu, Libo; Amine, Khalil; Zhang, Zhengcheng
Abstract In this study, UV‐curing was investigated as an alternative method to provide fast production of composite cathodes and significantly reduce the time and energy required for solvent removal in lithium‐ion battery fabrication. To serve our purpose, low‐molecular‐weight polysiloxane acrylate (PSA) was designed and synthesized from a polysiloxane epoxide precursor. In the presence of the acrylic acid additive LiNi1/3Mn1/3Co1/3O2 (NMC), electrode laminates containing 10 wt % PSA binder were successfully fabricated by UV‐curing. The cured electrode exhibited good mechanical and electrochemical properties. At current rates up to C/3, the cell performance of the UV‐cured NMC electrode was comparable to that of conventional polyvinylidene fluoride (PVDF)‐bound NMC electrode. Our initial success in applying high‐speed UV‐curing in composite electrode fabrication has proved that it is a promising route to substantially reducing the capital and operation costs of lithium‐ion battery electrode manufacturing and additionally bringing about important environmental benefits.